Concept of valid contract declaration of Waqf property in Islamic law - Ghazali, N.A.; Sipan, I.; Raji, Fauziah; Mohammad, Mohammad Tahir Sabit Haji (World Fatwa Management and Research Institute (INFAD), Universiti Sains Islam Malaysia (USIM), 2019)
Waqf plays an important role in improving public welfare in whole Islamic Countries. Therefore, waqf shall be conserved and permanently protected to keep its benefits for the public at all times. In order to develop the waqf property, it should be administered properly. Recognition of ownership on the property by effective contract of declaration is essential. Therefore, this paper focuses on the Islamic Law’s perspective regarding effective contract on a binding and valid declaration of waqf property in accordance to Islamic Law and other subsidiary sources as well as academic opinions. This paper also includes formalities of legally binding contract of waqf (waqafiah) on parties, formulated by earliest Muslim jurists. In addition, the detailed discussions on documents of waqf evidencing contractual transactions needed for registration of waqf property are included. The elements of valid and binding declaration of waqf or deeds discussed too. The approach adopted is ‘Content Analyses’.